Algoritmo quântico para o problema de gerenciamento de estoque - Fernandes, Gabriel Pedro Lima Moysés (Universidade Federal de São Carlos, 2023)
In this work, we developed a quantum algorithm in Adiabatic Quantum Computing for the Inventory Management Problem, adapted for factories that use gravitational shelves as the standard storage system. The main goal of the task is to determine the optimal allocation for inventory items on the warehouse shelves, minimizing the operational costs associated with the logistics of item input and output, while respecting the constraints involved. To achieve this, based on the pattern of item occurrences in the factory's demands, we devised a two-phase strategy that aims to determine the most efficient way to distribute items among the shelves. We constructed a set of Problem Hamiltonians that allow us to implement the strategy in the Adiabatic Quantum Computing model. Finally, we implemented the algorithm for a set of simple instances on D-Wave's quantum computers, a Canadian company that leads in developing devices suitable for Adiabatic Quantum Computing implementation, using a heuristic known as Quantum Annealing.
Quantum algorithm for inventory management problem
Keywords: Algoritmo quântico; Problema de gerenciamento de estoque; Computação quântica adiabática; Quantum annealing; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::FISICA CLASSICA E FISICA QUANTICA; MECANICA E CAMPOS